2013
DOI: 10.1155/2013/360607
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on the Correlation and Gender Difference between College Students’ Internet Addiction and Mobile Phone Addiction in Taiwan

Abstract: This study is aimed at constructing a correlative model between Internet addiction and mobile phone addiction; the aim is to analyse the correlation (if any) between the two traits and to discuss the influence confirming that the gender has difference on this fascinating topic; taking gender into account opens a new world of scientific study to us. The study collected 448 college students on an island as study subjects, with 61.2% males and 38.8% females. Moreover, this study issued Mobile Phone Addiction Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 49 publications
8
59
2
4
Order By: Relevance
“…) They play more often for excitement and for making friends than females. Females engage in gaming for passing time, social networking, texting, online shopping, but not for fighting or re‐enacting negative emotions . Wei et al .…”
Section: Resultsmentioning
confidence: 99%
“…) They play more often for excitement and for making friends than females. Females engage in gaming for passing time, social networking, texting, online shopping, but not for fighting or re‐enacting negative emotions . Wei et al .…”
Section: Resultsmentioning
confidence: 99%
“…Males may be at higher risk for PIU as compared to females. The exact reasons for observed gender-related differences in PIU-related behaviors are not well understood, and there have been differing results in the literature (Yau, Crowley, et al, 2012; Chiu, Hong, et al, 2013). Differences in preferred online activities may contribute to the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Shek et al conducted a study in high school adolescents of Hong Kong and found that internet addictive behavior was consistently high for male gender 10. Chiu et al conducted a study on internet addiction through smart phones in college students of Taiwan and found that female students were more addicted than male students 11. Malik et al conducted a research on students of University of Sargodha, Pakistan to study Facebook addiction and found no gender predominance 12.…”
Section: Discussionmentioning
confidence: 99%